Characteristics of optical flow from aerial thermal imaging, "thermal flow". Issue 5 (6th February 2022) - Nguyen, Tran Xuan Bach; Rosser, Kent; Perera, Asanka; Moss, Philip; Teague, Sam; Chahl, Javaan
Abstract: This study explores the utility of optical flow calculated from thermal imaging cameras, "thermal flow, " mounted on an aircraft for localization in day and night conditions. Our sensor implementation utilizes a long wave infrared (LWIR) micro sensor to capture sequences of thermal images and an on‐board computer to compute an optical flow estimate. We compared the performance of optical flow from the LWIR camera with the output of visible spectrum optical flow sensor. Flights were conducted spanning a 24 h window to explore how thermal flow performs relative to optical flow as the ground heats and cools. Agreement between optical and thermal flow was found during daylight when both sensors were functional. Additionally, thermal flow results were reliable in the middle of the day through to late evening, gradually degrading until shortly after sunrise.